Institutional marine affairs cooperation in developing state regions. - Kwiatkowska, Barbara (1990)
Identifies the main advantages and obstacles encountered by regional organizations in their efforts to advance North-South and South-South cooperation in marine affairs. Addresses the wide range of activities covered by the Indian Ocean Marine Affairs Cooperation Conference (IOMAC).